High-frequency Oscillatory Ventilation in Children: A 10-year Experience - Marta Moniz; Catarina Silvestre; Pedro Nunes; Clara Abadesso; Ester Matias; Helena Loureiro; Helena Almeida (Jornal de Pediatria, 2013)
Objectives: The aim of the study was to describe the experience with high-frequency oscillatory ventilation (HFOV) in a Portuguese Pediatric Critical Care Unit, and to evaluate whether HFOV allowed improvement in oxygenation and ventilation. Methods: This was a retrospective observational cohort study of children ventilated by HFOV between January, 2002 and December, 2011. The following parameters were recorded: demographic and clinical data, and blood gases and ventilatory parameters during the first 48 hours of HFOV. Results: 80 children were included, with a median age of 1.5 months (min: one week; max: 36 months). Pneumonia (n = 50; 62.5%) and bronchiolitis (n = 18; 22.5%) were the main diagnoses. Approximately 40% (n = 32) of the patients developed acute respiratory distress syndrome (ARDS). Conventional mechanical ventilation was used in 68 (85%) of patients prior to HFOV. All patients who started HFOV had hypoxemia, and 56 (70%) also presented persistent hypercapnia. Two hours after starting HFOV, a significant improvement in SatO2/FiO2 ratio (128 ± 0.63 vs. 163 ± 0.72; p < 0.001) that was sustained up to 24 hours of HFOV and a decrease in FiO2 were observed. Since the beginning of HFOV, the mean PCO2 significantly decreased (87 ± 33 vs. 66 ± 25; p < 0.001), and the pH significantly improved (7.21 ± 0.17 vs. 7.32 ± 0.15; p < 0.001). Overall survival was 83.8%. Conclusions: HFOV enabled an improvement in hypercapnia and oxygenation. It is a safe option for the treatment of ARDS and severe small airway diseases. Resumo: Objetivos: O objetivo do estudo foi descrever a experiência com ventilação oscilatória de frequência (VOAF) em uma unidade portuguesa de Cuidados Intensivos Neonatais e Pediátricos e avaliar se a VOAF permitiu uma melhoria na oxigenação e na ventilação. Métodos: Estudo de coorte retrospectivo observacional em crianças submetidas À ven- tilação com VOAF entre janeiro de 2002 e dezembro de 2011. Os seguintes parâmetros foram registrados: dados demográficos e clínicos; gases sanguíneos; e parâmetros venti- latórios durante as primeiras 48 horas de VOAF. Resultados: O estudo incluiu 80 crianças com uma idade média de 1,5 mês (mínima: uma semana; máxima: 36 meses). Pneumonia (n = 50; 62,5%) e bronquiolite (n = 18; 22,5%) foram os principais diagnósticos. Cerca de 40% (n = 32) dos pacientes desenvolveram a síndrome da angústia respiratória aguda (SARA). A ventilação mecânica convencional foi utilizada em 68 (85%) pacientes antes da VOAF. Todos os pacientes que começaram a VOAF tiveram hipoxemia, e 56 (70%) também apresentaram hipercapnia persistente. Duas horas após o início da VOAF, foi observada uma melhoria significativa na proporção SatO2/FiO2 (128 ± 0,63 em comparação a 163 ± 0,72; p < 0,001), que foi mantida durante as 24 horas de VOAF, e uma redução da FiO. Desde o início da VOAF, a PCO2 média teve uma queda significativa (87 ± 33 em comparação a 66 ± 25; p < 0,001) e o pH aumentou significativamente (7,21 ± 0,17 em comparação a 7,32 ± 0,15; p < 0,001). A sobrevida geral foi de 83,8%. Conclusões: A VOAF permitiu uma melhoria na hipercapnia e na oxigenação. Trata-se de uma opção segura no tratamento da SARA e de doenças graves das pequenas vias aéreas. Keywords: High frequency oscillatory ventilation, Child, Acute respiratory failure, Bronchiolitis, Pneumonia, Acute respiratory distress syndrome, Palavras-chave: Ventilação oscilatória de alta frequência, Criança, Insuficiência respiratória aguda, Bronquiolite, Pneumonia, Síndrome da angústia respiratória aguda